The fault position identification method for the outer ring of deep groove ball bearing in a wide range. (15th November 2022) - Zhang, Ke; Lu, Yanqiu; Shi, Huaitao; Bai, Xiaotian; Yuan, Zhenming
Highlights: The paper proposes a new fault position identification method of bearing outer ring, named horizontal-horizontal-vertical synchronous root mean square (HHVSRMS). The paper considers the attenuation of vibration signal when fault signal transmits along the outer ring of the bearing. The paper expands the fault identification range of bearing outer ring. Abstract: Fault position identification of bearing outer ring is of great significance to the fault diagnosis and the operating state prediction of bearing system. But the existing fault position identification method is limited by a small identification range. In this paper, a new fault position identification method of bearing outer ring is proposed, named horizontal-horizontal-vertical synchronous root mean square (HHVSRMS). Firstly, this method considers the attenuation of vibration signal when fault signal transmits along the outer ring of the bearing. The vibration signal of the measuring point is obtained by the dynamic model. Subsequently, the mapping relationship between the synchronous root mean square (SRMS) of vibration signals at three measuring points and the fault position is obtained through simulation analysis. On this basis, the fault position of bearing outer ring is identified. The HHVSRMS localization method expands the fault identification range of bearing outer ring to 230°∼310°. The feasibility of the method is verified by comparing simulation result with the experimental results.